Workplace gender inequality: case of General Post Office Kota Kinabalu, Sabah / Rozeiamy Md. Jali and Fazidah Mudin - Md. Jali, Rozeiamy; Mudin, Fazidah (2011)
The emergence of women movement to seek for equality already exists since the 19th century. Women had been oppressed since long ago and this kind of oppression always been given to the minority group, but women is not a minority group. Inequality towards women is assumed to happen because women is seen as weak, gracious, full of sympathy, and do not have the power in making decision. This kind of mind set always appears especially for those who think that they are more powerful than women. Women had realized that they should prove that they also can be relied on to make good decision to hold the same power as man. This is the kind of situation which provided the impetus for the movement where women seek for the equal opportunity. Since the ancient times, women had been considered second-class citizens whose existence was limited to interior life of the home, domestic chores, childbearing, and children care. They do not have the right to own property, maintaintheir wages, or sign contract (Dahlstrom & Liljestrom, 1983). Women are not given the opportunity to hold an important position.